Adriatic coast of Croatia and its hinterland from 50 000 to 25 000 BP - Karavanić, Ivor (Array, 2009)
This paper presents the recent analysis of the lithic artefacts from the upper layers (containing late Mousterian industry) from the site of Mujina Pećina, Dalmatia and the Aurignacian levels of the site of Šandalja II, Istria. Mousterian tools from Mujina Pećina are predominantly produced on local chert, with the occasional use of Levallois technology. Local chert is also predominant in the Aurignacian of Šandalja II where blades are produced using soft hammer percussion. Although in the Mousterian sequence of Mujina Pećina some Upper Paleolithic tool types are present, and in the Aurignacian levels of the Šandalja II Middle Paleolithic tool types are numerous, neither industry shows a progressive transitional nature.. Furthermore, no site in the eastern Adriatic region thus far documents the Middle/Upper Paleolithic transition and Aurignacian sites on the Adriatic coast of Croatia are very rare. Possible explanations include the rise of the sea level at the end of the Pleistocene, the lack of research/systematic survey in the region for sites of these periods and/or the low population density in this region during the Aurignacian.